PENGARUH STRATEGI PEMBELAJARAN AKTIF BERBASIS PENDEKATAN PMRI UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Anna Auliatur Rohmah; Abdur Rohim; Arezqi Tunggal Asmana (JEDMA Jurnal Edukasi Matematika, 2024)
This research aims to determine the effect of active learning strategies based on Indonesian Realistic Mathematics Education to improve students' understanding of concepts in quadratic function material. This research uses a quantitative approach with quasi-experimental research methods. The data collection technique used is the test technique. The data analysis technique uses the t-test. The results of the research showed that the average pretest score for the experimental class was 30,4 while the control class was 31,0. And the results of the post-test score for the ability to understand concepts for experimental class students were 83,3 while those for the control class were 67,9. Based on the results of post-test data analysis with a significance value (2-tailed) 0.001 <0.05. So it can be concluded that learning using active learning strategies based on the Indonesian Realistic Mathematics Education approach has an effect on increasing students' understanding of concepts.